Dieta del Suri, Rhea pennata (Orbigny, 1834) (Aves: Rheidae), en ecosistemas altoandinos de Moquegua, Perú - Echaccaya, Marli (2017)
We study the Lesser Rhea (Rhea pennata) diet in the Moquegua region of southern Peru, using analysis of feces. This species considered “Critically Endangered” in Peru, was shown as strictly herbivorous, mainly folivorous. A total of 44 plant morphospecies were identified in the diet, of which Oxychloe andina (a Juncaceae species dominant in disturbed wetlands of the Puna) had the highest values of relative density, weight, volume and frequency. Despite the apparent selectivity, this species presents a very diverse diet that would allow it to adapt to the nutritional deficiencies in the habitat that it occupies. The data obtained in different habitats of the Lesser Rhea show that in more arid zones there is a tendency for greater selectivity due to the presence of plant with secondary compounds (phenols, terpenes and alkaloids) to avoid herbivory, while in environments with wetlands (as the present study) the selectivity decreases, tending to feed on the dominant species.